Between disruptions and connections: "New" European Union migrants in the United Kingdom before and after the Brexit. Issue 1 (27th September 2018) - Lulle, Aija; King, Russell; Dvorakova, Veronika; Szkudlarek, Aleksandra
Abstract: This paper examines the pre‐ and post‐Brexit experiences and perspectives of migrants from three "new" European Union (EU) countries—Latvia, Poland, and Slovakia—who are living and working or studying in the London area. Deploying the key concepts of power‐geometry and relational space, the analysis explores the way that Brexit impacted the migrants' connections to the U.K. "bounded space" and their ongoing mobility behaviour and plans. Empirical evidence comes from 35 in‐depth interviews with migrants, most of whom were interviewed both before and after the referendum of June 23, 2016. We find that migrants are unequally positioned socio‐spatially to deal with the new power‐geometries resulting from Brexit, and we detect diverging trajectories between the more highly skilled and high‐achieving EU citizens and the more disadvantaged low‐skilled labour migrants. First, we probe the uncertainties brought about by juridical status, related to the length of stay in Britain. Second, we explore personal and professional connections and disruptions. Third, we question how the power‐geometries of time, juridical status, and personal/professional connections/disruptions shape future mobility plans.